2019
DOI: 10.3389/fonc.2019.01371
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Radiomics in Differentiation of Anaplastic Oligodendroglioma From Atypical Low-Grade Oligodendroglioma Using Machine-Learning Approach

Abstract: Objectives: To investigate the ability of radiomics features from MRI in differentiating anaplastic oligodendroglioma (AO) from atypical low-grade oligodendroglioma using machine-learning algorithms. Methods: A total number of 101 qualified patients (50 participants with AO and 51 with atypical low-grade oligodendroglioma) were enrolled in this retrospective, single-center study. Forty radiomics features of tumor images derived from six matrices were extracted from contrast-enhanced T1-weighted (T1C) images an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…The RQS of our study was satisfactory at 15 points (41.7% of the ideal quality score), and the detailed result is listed in 7. The RQSs of the relevant work (16)(17)(18)(19)(20) were analyzed in our study, but only our study is open to science and data, only one study conducted a multivariable analysis with non-radiomics features (20), and only one study based on multicenter validation (16). Besides, no research has conducted a phantom study, collected images of individuals at additional time points, discussed biological correlates, conducted a prospective study, or reported the cost-effectiveness of the clinical application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RQS of our study was satisfactory at 15 points (41.7% of the ideal quality score), and the detailed result is listed in 7. The RQSs of the relevant work (16)(17)(18)(19)(20) were analyzed in our study, but only our study is open to science and data, only one study conducted a multivariable analysis with non-radiomics features (20), and only one study based on multicenter validation (16). Besides, no research has conducted a phantom study, collected images of individuals at additional time points, discussed biological correlates, conducted a prospective study, or reported the cost-effectiveness of the clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…It has great potential for oncology practice, including differential diagnosis, prediction of pathological classification, lymph node metastasis, and survival (6)(7)(8)(9)(10). Radiomics has been applied to brain tumor diseases (11)(12)(13)(14)(15), especially in differentiating brain tumors (16)(17)(18)(19)(20)(21). For example, Qian et al investigated the ability of radiomic analysis to distinguish between isolated brain metastases and glioblastoma (16); Dong et al used the radiomic features derived from the areas of peripheral enhancing edema to differentiate glioblastoma from supratentorial single brain metastasis (17); Zhang et al investigated the feasibility of contrast-enhanced T1WI radiomics features extracted by machine-learning algorithms to distinguish between low-grade oligodendroglioma and atypical anaplastic oligodendroglioma (18); Chen et al applied radiomics analysis to distinguish between metastatic brain tumors and glioblastomas based on contrast-enhanced T1WI, and they validated the discriminative performance of this method (19); Artzi et al used radiomics-based machine learning to differentiate between brain metastasis subtypes and glioblastoma based on conventional postcontrast T1WI (20).…”
Section: Introductionmentioning
confidence: 99%
“…Ni et al achieved a general accuracy of 84.48% when using radionics analysis based on the LASSO + GBDT method for the noninvasive diagnosis of microvascular invasion in hepatocellular carcinoma [34]. Zhang et al used LASSO + GBDT to examine the ability of radionics characteristics from MRI in differentiating anaplastic ol igoden drogl ioma (AO) f ro m a ty pi cal l ow-grade oligodendroglioma (35). The majority of researchers have performed quantitative analysis of multi-modality image data for diagnosis and prognosis by using artificial intelligence methods, but few of them have focused on the routine laboratory tests that easily obtained from clinic.…”
Section: Discussionmentioning
confidence: 99%
“…21,[37][38][39][40] In some other studies, radiomics and ML methods were combined to analyze the imaging phenotype of tumors with other cancers, which showed good results. [41][42][43][44][45] Here, we used 5 ML methods to identify the Medical Physics, 47 (8), August 2020 differences in imaging phenotypes in various states of EGFR, and determined the best-performing method. Among the above-mentioned studies of lung adenocarcinoma EGFR mutations, only Rios et al used data from different institutions, revealing an AUC of 0.75 and accuracy of 0.65.…”
Section: Discussionmentioning
confidence: 99%